Unveiling Effective Employee Retention Strategies in Surabaya's Shopping Center Industry: Insights from Employee Perspectives: Mengungkap Strategi Retensi Karyawan yang Efektif di Industri Pusat Perbelanjaan Surabaya: Wawasan dari Perspektif Karyawan - Novianto, Iful; Rizqiawan, Hendrik; Indrawati, Trisa (Universitas Muhammadiyah Sidoarjo, 2023)
This study analyzed the most effective employee retention strategies for the shopping center industry in Surabaya, a major city in ASEAN. The research involved interviewing 13 employees with at least one year of experience in shopping centers across different areas of the city. The research approach used was qualitative. Based on employee perspectives, the factors that could help shopping center companies develop an effective employee retention strategy are salaries, bonuses & incentives, insurance, career paths, job plans, training, and employee facilities. The study aimed to develop an employee retention strategy model that can be used by shopping centers in Surabaya. Highlights: The research employs a qualitative approach and conducts interviews with 13 employees from shopping centers in Surabaya to investigate employee retention strategies. The study aims to identify the factors that shopping center management should consider in implementing effective employee retention strategies from the employees' viewpoint. Various factors that can influence employee retention are identified, such as salary, bonuses and incentives, insurance, career advancement opportunities, job design, training, and employee facilities. Employee facilities, including regular recreational activities to foster better relationships among employees and management, as well as designated parking spaces for employees, are considered important factors in employee retention strategies. Keyword: Employee Retention Strategy, Shopping Center Industry, Surabaya, Qualitative Research, Factors